Meter in Music, 1600-1800 : Performance, Perception, and Notation - Houle, George (Book collections on Project MUSE., 1987)
While the notation of 17th- and 18th-century music looks familiar, its meanings and the treatment of meter in performance have evolved dramatically. When performed according to the conventions of its own time, the music of 1600-1800 balances precision and flexibility, with an enchanting lilt, grace, and vitality. With many quotations and musical examples from theoretical treatises and instruction manuals of the period, Meter in Music is a practical guide to the performance of Baroque and early Classical music, with guidance on notes iňgales, fingerings, bowings, and woodwind tonguings.